2021
DOI: 10.3892/br.2021.1496
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A, ferritin and carcinoembryonic antigen as biomarkers of severity in patients with COVID‑19

Abstract: In view of the rapid spread of COVID-19 and the high mortality rate of severe cases, reliable risk stratifying indicators of prognosis are necessary to decrease morbidity and mortality. The aim of the present study was to evaluate the value of serum amyloid A (SAA) and carcinoembryonic antigen (CEA) as prognostic biomarkers in comparison to other predictors, including C-reactive protein (CRP) and ferritin levels. This study included 124 patients diagnosed with COVID-19, and they were assigned to one of two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
4
5
0
Order By: Relevance
“…Carubbi et al [36] found that ferritin levels are not associated with a worse prognosis but correlate with the extensiveness of lung involvement. Compared to SAA, ferritin had lower prognostic utility in our study, which is consistent with previous studies [37] [38] . An interesting study by Abdelhakam et al [37] showed that a combination of SAA and ferritin improved the performance characteristics of SAA by increasing AUC from 0.928 to 1.000 and sensitivity from 98.5 to 100%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Carubbi et al [36] found that ferritin levels are not associated with a worse prognosis but correlate with the extensiveness of lung involvement. Compared to SAA, ferritin had lower prognostic utility in our study, which is consistent with previous studies [37] [38] . An interesting study by Abdelhakam et al [37] showed that a combination of SAA and ferritin improved the performance characteristics of SAA by increasing AUC from 0.928 to 1.000 and sensitivity from 98.5 to 100%.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to SAA, ferritin had lower prognostic utility in our study, which is consistent with previous studies [37] [38] . An interesting study by Abdelhakam et al [37] showed that a combination of SAA and ferritin improved the performance characteristics of SAA by increasing AUC from 0.928 to 1.000 and sensitivity from 98.5 to 100%.…”
Section: Discussionsupporting
confidence: 93%
“…Pieri et al 12 detected significant persistent elevation of SAA among non survivors compared to survivors. Abdelhakam et al 25 and Li et al 13 reported significant correlation between SAA and severity of radiological involvement. Our findings pointed out a significant increase in serum amyloid A in all children hospitalized with COVID-19.…”
Section: Discussionmentioning
confidence: 96%
“…In all relevant studies, the hemoglobin levels were found to be lower in severe groups than those in controls [7,10,24] or non-severe groups [22,[25][26][27][28][29]. However, in the comparisons between severity [7,10,15,[17][18][19]23,24,[30][31][32][33][34][35][36][37] and mortality [10,30,[38][39][40][41], there was not a consistent numerical magnitude relationship between them. In addition, studies on TIBC [8,10,12,13] and TSAT [8,13] only refer to mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Lower levels of hepcidin in cases than controls was documented in a study [10], whereas the other studies reported an inverse result [18,20,24]. Unusually, more dangerous groups had higher ferritin levels in almost all relevant comparisons [4,6,[10][11][12][13][14][15][17][18][19][20][21][22][24][25][26][27][28][29][30]32,[34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%